Cyclic mechanical stretch regulates the AMPK/Egr1 pathway in tenocytes via Ca2+-mediated mechanosensing. (2nd November 2022) - Huang, Yu-Ting; Wu, Yu-Fu; Wang, Hsing-Kuo; Yao, Chung-Chen Jane; Chiu, Yi-Heng; Sun, Jui-Sheng; Chao, Yuan-Hung
ABSTRACT: Purpose: Mechanical stimuli are essential for the maintenance of tendon tissue homeostasis. The study aims to elucidate the mechanobiological mechanisms underlying the maintenance of tenocyte homeostasis by cyclic mechanical stretch under high-glucose (HG) condition. Materials and methods: Primary tenocytes were isolated from rat Achilles tendon and 2D-cultured under HG condition. The in vitro effects of a single bout, 2-h cyclic biaxial stretch session (1 Hz, 8%) on primary rat tenocytes were explored through Flexcell system. Cell viability, tenogenic gene expression, intracellular calcium concentration, focal adhesion kinase (FAK) expression, and signaling pathway activation were analyzed in tenocytes with or without mechanical stretch. Results: Mechanical stretch increased tenocyte proliferation and upregulated early growth response protein 1 (Egr1) expression. An increase in intracellular calcium was observed after 30 min of stretching. Mechanical stretch phosphorylated FAK, calmodulin-dependent protein kinase kinase 2 (CaMKK2), and 5' adenosine monophosphate-activated protein kinase (AMPK) in a time-dependent manner, and these effects were abrogated after blocking intracellular calcium. Inhibition of FAK, CaMKK2, and AMPK downregulated the expression of Egr1. In addition, mechanical stretch reinforced cytoskeletal organization via calcium (Ca2+)/FAK signaling. Conclusions: Our study demonstrated that mechanical stretch-induced calcium influx activated CaMKK2/AMPK signaling and FAK-cytoskeleton reorganization, thereby promoting the expression of Egr1, which may help maintain tendon cell characteristics and homeostasis in the context of diabetic tendinopathy.